TQM-BASED WEB APPLICATION FOR OPTIMIZING ACADEMIC PLACEMENT ASSESSMENTS - Holifah; Fatimatul Husna (International Journal of Multidisciplinary Reseach, 2025)
This study aims to develop and analyze the effectiveness of a Total Quality Management (TQM)-based web application in optimizing academic placement assessments in Islamic boarding schools. The background of this study is based on general problems related to the low efficiency and accuracy of the manual placement test process. The study was conducted at the Darul Lughoh Islamic Boarding School using a descriptive qualitative approach. Data collection techniques include in-depth interviews, participant observation, and documentation, which are analyzed using the Miles interactive model, as well as the approaches outlined by Huberman and Saldaña (2014). The results of the study indicate that the implementation of a TQM-based system can improve the efficiency of assessment implementation, the accuracy of student placement based on initial competencies, and strengthen teacher and student participation in the entire assessment process. In addition, this system reflects TQM principles such as customer focus, continuous improvement, and data-driven decision making, which contribute to the creation of more measurable, transparent, and sustainable academic governance. These findings reinforce the urgency of developing a quality-based digital assessment system as a strategy to improve the quality of Islamic education. This study also recommends replication of similar models in other educational institutions as part of adaptive and technology-based academic management reform.